PECULIARITIES OF THE PERSONAL AND CREATIVE COMPONENT IN PROFESSIONAL AND PEDAGOGICAL CULTURE OF HIGH SCHOOL TEACHERS - Демченко, Н. І. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2015)
The article deals with vocational and pedagogical culture of the high school teacher as an integral personal quality of the teacher-professional, as a condition and prerequisite for effective teaching activities, as a generalized indicator of the teacher`s professional competence and the goal of his or her professional self-improvement. It was determined that professional and pedagogical culture of the high school teacher is a way of creative self-realization of an individual teacher in various kinds of educational activities and communication aimed at the development, transfer and creation of pedagogical values and technology